Pengaruh Kualitas Layanan dan Kualitas Produk Terhadap Kepuasan Pelanggan pada Pandan Wangi Catering - Stenly Lube; Aftoni Sutanto; Riduwan (MES Management Journal, 2025)
This study aims to determine the effect of service quality and product quality on customer satisfaction at Pandan Wangi Catering. The type of research conducted is quantitative research. The population and sample in this study consist of 132 customers of Pandan Wangi Catering, using primary data collected through purposive sampling methods. The criteria for respondents in this study are individual or institutional customers who have placed orders at Pandan Wangi Catering during the 2021–2023 period and have made more than one purchase. The data analysis technique used in this research is multiple linear regression. The results of the study indicate that: 1) Service quality and product quality collectively have a positive and significant effect on customer satisfaction at Pandan Wangi Catering, confirming the first hypothesis of this research. 2) Service quality individually has a positive and significant effect on customer satisfaction at Pandan Wangi Catering in Bantul, confirming the second hypothesis of this research. 3) Product quality individually has a positive and significant effect on customer satisfaction at Pandan Wangi Catering, confirming the third hypothesis of this research.